2024
DOI: 10.1088/1402-4896/ad2419
|View full text |Cite
|
Sign up to set email alerts
|

A review on ionothermal synthesis of zeolites and zeotype materials

Wissam Fortas,
Bouhadjar Boukoussa,
Mohamed Abdelkrim Hasnaoui
et al.

Abstract: Known as green inorganic products and environmentally beneficial, ionic liquids (ILs) are increasingly used in the ionothermal synthesis of zeolites and zeotype materials compared to the hydrothermal method. This safe and successful process offers new opportunities to produce several molecular sieves with different morphologies and structures for promising applications.
In this review, we summarize the history of the most successful phases of zeolites and zeotype materials, with different structures su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 145 publications
0
2
0
Order By: Relevance
“…Among these techniques, liquid-liquid extraction and extractive distillation recognized as efficient methods, which are dictated by the selection of suitable extractants. In recent years, ILs, an environmentally friendly and effective extractants, have drawn intensive studies [11][12][13][14][15][16][17][18]. However, up to now, few studies have reported on the separation of 2-propanol and nhexane mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…Among these techniques, liquid-liquid extraction and extractive distillation recognized as efficient methods, which are dictated by the selection of suitable extractants. In recent years, ILs, an environmentally friendly and effective extractants, have drawn intensive studies [11][12][13][14][15][16][17][18]. However, up to now, few studies have reported on the separation of 2-propanol and nhexane mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…To minimize their inhalation, cigarette filters have been developed to utilize a variety of porous materials [4] such as fibrous cellulose [5], molecular sieves [6], resins, and molecularly imprinted polymers [7]. Ideally, the porous structures should allow good air permeation and minimize the passage of harmful substances; they are designed to block particulate matter like tar particles by size-dependent sieving, to arrest volatile molecules by specific or nonspecific adsorption, and to decompose the toxic targets into benign molecules on catalytically active sites [4,8]. It is highly desirable to understand the mass transport and adsorption/desorption of particles and molecules therein.…”
Section: Introductionmentioning
confidence: 99%